2022
DOI: 10.1088/1402-4896/ac8c70
|View full text |Cite
|
Sign up to set email alerts
|

First principles calculations to investigate Li-based quaternary Heusler compounds LiHfCoX (X = Ge, Sn) for thermoelectric applications

Abstract: In the last few decades, the varieties of semiconductors have been explored for electronic and thermoelectric applications. As per such motivations, in present research work, the investigation of two quaternary Heuslers (QHs) i.e. LiHfCoGe and LiHfCoSn (having semiconducting nature) have been carried out for structural, electronic, vibrational, elastic, mechanical, thermodynamical and thermoelectric properties within the computational approach of Density Functional Theory (DFT) and Boltzmann transport equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
(77 reference statements)
2
7
1
Order By: Relevance
“…Figure 2, shows that the systems under our investigation crystallizes in T-3 configuration which is analogous and closely related to Li-based QHA studied by Kaur et al [23]. In this theoretical study they have reported the T-3 configuration is the most stable atomic arrangement for LiHfCoGe and LiHfCoSn with corresponding optimized lattice constants 6.059 Å and 6.290 Å.…”
Section: Structural Propertiessupporting
confidence: 78%
See 3 more Smart Citations
“…Figure 2, shows that the systems under our investigation crystallizes in T-3 configuration which is analogous and closely related to Li-based QHA studied by Kaur et al [23]. In this theoretical study they have reported the T-3 configuration is the most stable atomic arrangement for LiHfCoGe and LiHfCoSn with corresponding optimized lattice constants 6.059 Å and 6.290 Å.…”
Section: Structural Propertiessupporting
confidence: 78%
“…In our case, the corresponding number of valence electrons contributed from the individual Na, Hf, Co, Rh, Ir, and Ge-atoms are 1, 4, 9, 9, 9, and 4 respectively, leading to M t = 0 for NaHfXGe compounds. Similar to those reported for the Li-based QHA [23]. The semi-conducting nature of QHAs are proven by performing the spin-polarized calculation based on the GGA formalism where the total magnetic moment is founf tpo be 0 µ B .…”
Section: Electronic Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…Several theoretical as well as experimental studies have been conducted recently to gain insight into the electronic behavior as well as the thermoelectric behavior of these systems. [10][11][12][13][14] First-principles calculations were utilised by Haleoot et al (2020) to analyse the exceptional thermoelectric and thermodynamic properties of the Quaternary Heusler (QH) compounds CoFeYGe (Y = Ti, Cr). 15 Density functional theory (DFT) has been used to examine another novel quaternary Heusler compound, CrVNbZn, which has the space group 216 (of cubic geometry) and shows maximum ZT = 0.79 in the wide temperature range of 260 K to 480 K as well as excellent electronic and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%